Characterization of Gomphrena globosa L. Flower Extract and Anti-Acne of Formulated Cream Against Cutibacterium acnes - Wuryanto, Stefani Alya Swasa; Damayanti, Ida Ayu Manik; Indrayoni, Putu (Sciences of Pharmacy, 2026)
Cutibacterium acnes is a cause of acne. Conventional treatments often lead to side effects and bacterial resistance, necessitating natural alternatives. Globe Amaranth (Gomphrena globosa L.) shows potential as an anti-acne agent. This study employed an in vitro experimental laboratory design to evaluate the anti-acne activity of G. globosa L. flower extract formulated cream against C. acnes using the well diffusion method. Antibacterial activity was tested using KN (base cream), KP (1% clindamycin cream), F1 (10%), F2 (15%), and F3 (20%), and the data were analyzed using SPSS statistical analysis. Results indicated that the ethanolic extract of GA flowers has an IC50 of 85.483 ppm, TPC of 60.456 ± 0.589 mg GAE/g, and TFC of 34.390 ± 0.989 mg QE/g. It exhibited antibacterial activity against C. acnes, with inhibition zone diameters of 6.693 ± 0.2 mm for the 15% formula and 7.382 ± 0.22 mm for the 20% formula. The antibacterial activity is believed to be driven by the presence of secondary metabolites, particularly phenols and flavonoids identified in the extract.